Numerical and Field-Based Analysis of Soil Nailing for Slope Stability - Adolf Situmorang; Anik Kustirini; Kukuh Wisnuaji Widiatmoko (Universitas Semarang, 2025)
Landslide occurrences in Indonesia are predominantly associated with soft soils and inadequate drainage conditions during periods of high-intensity rainfall. Nevertheless, the country’s diverse geological settings pose significant challenges for implementing effective landslide mitigation strategies, particularly as most existing studies are concentrated on specific islands, each characterized by distinct geotechnical and geomorphological conditions. In certain areas of Flores Island, landslides have been observed at relatively shallow depths and steep slope angles, often occurring in remote locations. Additionally, the tectonic setting of Flores Island—surrounded by multiple active seismic sources—increases the susceptibility to both rockfalls and earthquake-induced landslides. Soil nailing has emerged as a promising stabilization technique in such conditions, particularly where subsurface materials exhibit high resistance to penetration (N-SPT > 60). Despite the steep terrain, the technique remains viable due to its adaptability and minimal disturbance to the existing slope geometry. Stability analyses conducted using both the FEM and LEM under static loading conditions indicate that soil nailing is effective in reinforcing the slope without inducing significant deformation. Furthermore, the reinforced slopes demonstrate sufficient stability under seismic loading, satisfying the design earthquake criteria stipulated by the Indonesian Standard.